Retention of CAD-CAM locator retentive attachment insert in mandibular implant overdenture - Mai Hassan Diab; Medhat Sameh Abdelaziz; Mohamed Hatem Kamal Eldin (BMC Oral Health)
Abstract Background The continuous development in digital prosthodontics allowed the customization of attachments and retentive inserts which offers an easy and cheap solution for regular maintenance of locator overdentures during daily practice. The present study compared the change in retention values of the fully digitally manufactured custom-made locator attachment retentive insert with the ready-made ones after insertion, removal, and masticatory cycles. Methods A complete denture was constructed over a mandibular edentulous epoxy model. Two implants were inserted into the model between the laterals and canines following the prosthetically driven implant protocol. Locator retentive attachment inserts were digitally designed using free-form modeling software and milled from PEEK (Poly Ether Ether Ketone). After the pick-up of the ready- and custom-made retentive inserts, an insertion, removal, and masticatory cycles test simulating 1 year of patient usage was performed. The change in retention values was recorded at baseline, 6 months, and after one year of simulated clinical use. An independent sample t-test was used to compare the data between the two studied groups. Results There were statistically significant differences in retention values between the custom-made and ready-made locator inserts at baseline and after 6 months. (p = 0.001*). On the other hand, there was no significant difference in retention after 1 year of simulated use. (p = 0.083, NS) Conclusions The custom-made milled locator retentive attachment insert can be used as an alternative to the ready-made one due to their comparable retention values after 1 year of simulated use.